1995
DOI: 10.1093/rheumatology/34.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Defective Spontaneous and Bacterial Lipopolysaccharide-Stimulated Production of Interleukin-1 Receptor Antagonist by Polymorphonuclear Neutrophils of Patients With Active Systemic Lupus Erythematosus

Abstract: Interleukin-1 receptor antagonist (IL-1ra) binds competitively to IL-1 receptors but does not transduce the signal which blocks the biological activities induced by IL-1. In this study, polymorphonuclear neutrophils (PMN) and mononuclear cells (MNC) from the patients with active systemic lupus erythematosus (SLE) (n = 11), inactive SLE (n = 13) and normal individuals (n = 13) were compared for the IL-1ra producing capacity of these cells. PMN and MNC at a concentration of 1 x 10(6) cells/ml were incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…3 However, patients with systemic lupus erythematosus (SLE) may have intrinsically increased risks for infections due to impaired function of polymorphonuclear neutrophils and functional hyposplaenia that may be further exacerbated by immunosuppressants. [4][5][6] Several studies have evaluated infections in SLE patients attending general rheumatology clinics or during hospitalizations [7][8][9][10][11][12][13][14][15][16] ; however, SLE patients with extra-renal manifestations have different therapeutic profiles compared to patients treated for LN. 17,18 In addition, active renal disease is also a risk factor for infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, patients with systemic lupus erythematosus (SLE) may have intrinsically increased risks for infections due to impaired function of polymorphonuclear neutrophils and functional hyposplaenia that may be further exacerbated by immunosuppressants. [4][5][6] Several studies have evaluated infections in SLE patients attending general rheumatology clinics or during hospitalizations [7][8][9][10][11][12][13][14][15][16] ; however, SLE patients with extra-renal manifestations have different therapeutic profiles compared to patients treated for LN. 17,18 In addition, active renal disease is also a risk factor for infection.…”
Section: Resultsmentioning
confidence: 99%
“…Hence proliferative LN is usually treated aggressively with immunosuppressive therapy, such as a combination of high dose glucocorticoids and a cytotoxic agent . However, patients with systemic lupus erythematosus (SLE) may have intrinsically increased risks for infections due to impaired function of polymorphonuclear neutrophils and functional hyposplaenia that may be further exacerbated by immunosuppressants . Several studies have evaluated infections in SLE patients attending general rheumatology clinics or during hospitalizations; however, SLE patients with extra‐renal manifestations have different therapeutic profiles compared to patients treated for LN .…”
mentioning
confidence: 99%
“…Additionally, the endothelial isoform of IL-8 appears to have a variety of tissue-protective effects, such as mediating normal wound healing, decreasing scar formation, tissue remodeling through endothelial proliferation, myocardial protection during ischemiareperfusion injury, and maintenance of normal glomerular architecture [31][32][33][34]. Finally, neutrophils from patients with active SLE demonstrate a defect in IL-8 production that resolves with successful therapy [35]. It is thus conceivable that after acutely initiating inflammation at sites of tissue injury, which is likely beneficial, further induction of IL-8 by Nrf2 serves to attenuate neutrophil-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have indicated that exaggerated or reduced rates of spontaneous neutrophil activation are linked to viral [13] or autoimmune conditions [14], implying a physiological function for spontaneous neutrophil activation. Spontaneous and stimulated activation of neutrophil oxidative metabolism has been extensively documented in-vitro [1518].…”
Section: Introductionmentioning
confidence: 99%